Analysis of The Level of Satisfaction of Researchers and Devotioners with The Performance - Suprapti, Suprapti; Ardiansari, Anindya; Waluyo, Soleh Adi; Suryaningrum, Lubuk Novi; Apriyanti, Rita; Permatahati, Martinda Intan (Universitas Negeri Semarang, 2023)
The development of information systems and technology has certainly changed people's behavior in carrying out their activities which were initially carried out manually and can now be carried out digitally so that they are more effective and efficient. The Service Research Information System (SIPP) is a transformation carried out to digitize research and service services within the Semarang State University (UNNES). As a service provider, to find out whether the UNNES Service Research Information System (SIPP) is running as it should, an evaluation process is needed on the performance of the information system. In carrying out information system analysis and evaluation activities, the PIECES Framework analysis model is used. PIECES framework is a framework that has six categories for classification and problem solving, namely Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. The use of the PIECES framework method is very suitable for analyzing each system variable studied because it can provide real results on the effectiveness of the system used by UNNES. The aim of this research is to measure the level of satisfaction, find out strengths and weaknesses, analyze what components need to be improved in the quality of service at SIPP.